Pembentukan Karakter Peduli Lingkungan Melalui Program Sekolah Bijak Sampah Pada Generasi Hijau - Nur Hidayatil Janah; Febrian Alwan Bahrudin; Dinar Sugiana Fitrayadi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study highlights the growing urgency of environmental issues, which need immediate attention. One of the biggest challenges is the lack of environmental awareness, which makes living conditions less comfortably. The study aims to: (1) understand the current level of environmental awareness among the younger generation, and (2) analyse how the Waste-Wise School Program helps shape environmentally responsible behaviour in students. This research uses a qualitative method with a descriptive approach, in which data were collected through observations, interviews, and documentation from those involved in the program. The Waste-Wise School Program is seen as one way to address the environmental awareness crisis. The study results show that first, environmental awareness character has developed due to technological advancements, facilitating access to information sources; second, character building for environmental awareness in the green generation is cultivated through the Waste-Wise School Program through real and practical actions, helping the green generation to easily understand how the smart waste school program works. The green generation who participated in the Waste-Wise School Program serves as role models to raise awareness about the importance of environmental awareness character, which ensures lasting comfort.